Pigeon pea initial growth under different concentrations of aluminum and commercial substrate - Rodrigues, Gustavo Araujo; Pereira, Breno de Jesus [UNESP]; Santos, Anacleto Ranulfo dos; Costa, Francielle Medeiros; Anjos, Gilvanda Leo dos (Univ Estadual Mato Grosso Sul, 2020)
The incorporation of organic substrate into the soil can reduce aluminum toxicity in pigeon pea (Cajanus cajan (L.) Millsp.) plants, making it a viable alternative for use by small farmers in acidic soil regions such as the northeast semi-arid regions of Brazil that contain toxic aluminum in the soil. The aim of this study was to evaluate the effect of increasing aluminum doses and different commercial substrate concentrations on the initial growth of the pigeon pea. The experiment was undertaken in a greenhouse using a completely randomized design with a 5 x 3 factorial scheme. The first factor consisted of five doses of aluminum (0, 13.5, 27, 54, and 108 mg L-1) and the second factor consisted of three percentages of commercial substrate Vivato Slim Pro (R) (0%, 10%, and 20%), with five replicates per treatment, totaling 60 experimental units. The variables evaluated were plant height; total chlorophyll; shoot, root, and total dry matter; and root volume. The use of the commercial substrate attenuated the aluminum toxicity and favored the initial growth of pigeon pea plants, regardless of the concentration used. Thus, the aluminum was detrimental to the initial plant growth at all tested concentrations and showed more pronounced signs of toxicity on the root volume.
Keywords: Cajanus cajan; acid soils; toxicity